So You, My Children, Can Have a Better Life: A Cambodian American Perspective on the Phenomenology of Intergenerational Communication about Trauma. Issue 4 (20th April 2016) - Lin, Nancy J.; Suyemoto, Karen L.
ABSTRACT: We address this question: How do Cambodian American young adults come to know about their family's experiences of trauma? Using a social constructivist critical ideological approach, we developed a phenomenological model describing intergenerational communication about trauma (IGCT) in Cambodian American families. We found IGCT to be an interactional process in which younger and older generations each played a role. IGCT was influenced by the availability of multiple sources of information and opportunities for learning, interpersonal connectedness between the generations, emotional distress tolerance, and having motivation to empathically learn and share. When these factors were abundant, direct interactive IGCT was more likely. When wanting, the IGCT was more disrupted and incoherent, filled with emotionally charged silence and lead to negative attributions. IGCT was a dynamic process that could change over time to accommodate developmental change. Limitations of the findings, clinical implications, and future directions are discussed.